Checklist of epiphytic lichens on "Quercus ilex" subsp. "rotundifolia" from Vall d’Albaida (Valencia, Spain) - Garrido-Benavent, Isaac; Llop, Esteve; Gómez-Bolea, Antonio (Botanica Complutensis, 2013)
A catalogue of 55 lichens growing on bark of holm-oak (Quercus ilex subsp. rotundifolia) and 2 lichenicolous fungi is compiled from oneof the most eastern areas of Betic Range. The area is characterized by an intensive agriculture since long.